Who Left the Dog Out (of the History)? - : Capnocytophage Canimorus Baceteremia Induced Sepsis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Internal Medicine; Case Report